Study of Synthetic Fertilizer Chili and Organic Fertilizer Watermelon on Relay Cropping Fields - Saputro, Avisema Sigit; Hayati, Dewi Ratna Nur (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2023)
Chili is an agricultural commodity with prices that tend to fluctuate. Chilli-watermelon relay cropping is one way to overcome this problem and reduce losses when chili prices fall. Watermelon has a relatively short lifespan, so it can be a substitute when chili prices fall. Chili and watermelon are almost the same age. This research aims to assess how well the tandem cultivation of chili and watermelon in a relay cropping system is performed. The study employed a factorial randomized block design for experimentation. The research consisted of 2 experiments, namely chili and watermelon, cultivated on the same land. Experiment with 2 factors in chili, namely variety and type of NPK. The watermelon experiment involved 2 factors: variety and concentration of liquid organic fertilizer. All experiments were repeated four times. The data analysis proceeded by conducting Duncan's multiple range test at a significance level of 5%. Parameters for observing plant height, when flowers appear, fruit weight, number of chilies per plant, and watermelon fruit circumference. The results showed that chili and watermelon relay cropping could be harvested simultaneously without competition between plants. There was no interaction between chilies and watermelon. Chili has the highest weight in the Colombus variety with NPK Mahkota fertilizer. The watermelon with the highest weight was in the Baginda variety, with a liquid organic fertilizer concentration of 60 ml/liter. The relay cropping of chili and watermelon plants was effective simultaneously, and there was no decrease in yield.